Frequency, histopathological findings, and clinical significance of cervical heterotopic gastric mucosa (gastric inlet patch): a prospective study in 300 patients - Weickert, Uwe; Wolf, A.; Schröder, C.; Autschbach, Frank; Vollmer, H. (Diseases of the esophagus, 2011)
The frequency and clinical significance of heterotopic gastric mucosa in the upper esophagus is not sufficiently known. Heartburn or dysphagia could result from mucin and/or acid production in this area. We undertook a prospective study in 300 patients with special attention of the endoscopist to this area. Moreover, clinical symptoms were determined by questionnaire before performing endoscopy. A total of 33/300 (11%) of patients had at least one histologically proven gastric inlet patch without gender or age preference. In 20/33 (61%) cases, the heterotopic gastric mucosa was classified as mixed type, in 8/33 (24%) as oxyntic, and in 5/33 (15%) as mucoid. Helicobacter pylori was present in none of the cases. There was no significant association to the presence of a hiatal hernia, reflux esophagitis, Barrett’s esophagus, or gastric/duodenal ulcer. Moreover, there was no association to the reported grade of heartburn in the upper or lower part of the esophagus, recurrent hoarseness, or dysphagia. When thorougly performed, heterotopic gastric mucosa is a quite frequent finding in endoscopy of the upper gastrointestinal tract. The presence of this gastric mucosa in the upper third of the esophagus seems to be rarely the cause of clinical symptoms and little prone to complications.